The Prevalence of Brucella Agglutinins in Karadach District Among Human, Goats & Sheep - Shareef, Jalal M.; Abdi, Abas A.; Maroof, Ari S.; Saeed, Aras M. (Sulaimani Journal for Pure and Applied Sciences, 1999)
A preliminary investigation on the prevalence of Brucella agglutinins among farmers and animals was carried out during a 6 months period (Feb - July / 1995). 2131 blood samples were collected from man and animals, including goats, sheep and only 4 cattle. Sera were separated for both card and tube agglutination test. Out of 215 human serum samples 118(54.8%) and 85 (39.53%) were positie by card test and tube agglutination test respectively, 520 (27.13%) and 374 (19.51%) positive serum by above tests were shown respectively from a total of 1916 animal sera. The economical and public health hazards of brucellosis are highlighted, the essential investigation and further studies for a control program and eradication of this disease are also discussed.